Topical symbols of Kyiv as a tourism brand - Afanasiev, Illia; Ustymenko, Lesia; Malynovska, Oksana; Stafiichuk, Valentyn; Bulhakova, Nataliia (Linguistics and Culture Review, 2021)
The attention to branding, from theorists as well as from practitioners, had been remained at a very high level for the 2000s and 2010s. There many new branches of branding theory have emerged, and place branding was among them. Actually, place branding has become an umbrella term, a generic definition for three areas of study and practice: nation branding, region branding, and city branding. Every year, new scientific, journalistic, business articles and books on place branding emerge, there are even several specialized periodicals devoted to this field of branding. This study aims to identify the most relevant and effective symbol of the Ukrainian capital city Kyiv (Kiev) as a tourism brand. Questionnaire surveys and the content analysis of literature and mass media are used. Key segments and sub-segments of the target audience of Kyiv tourism branding are determined, as well as the key factor of influence on the formation of the opinion regarding the tourism symbols of Kyiv. The most common popular symbol is compared with the real resources of the city. Thus, a set of relevances is found appropriate for the development of effective branding of Kyiv.